PENERAPAN MEDIA ULAR TANGGA DALAM PENGENALAN MATEMATIKA DI KOMUNITAS SAUNG HARMONI SAMBIDOLAN - Sugeng Riyadi; Ida Khotimah; Dien Muhammad Ismal Bransika (AbdiMasya | Hira Institute, 2024)
Saung Harmony Sambidolan is a community that provides knowledge outside of school hours. This saung is not tied to the curriculum; the rules used are flexible and are in the form of habits that are considered suitable to teach to children. The results of observations carried out by KKN-PPM students at Merangin University found that the children's interest in mathematics was very low, and the children's mindset towards mathematics had shifted to a harmful level. For this reason, it is necessary to provide additional tutoring in mathematics subjects with the aim of increasing students' interest in learning mathematics subjects and improving children's mindsets towards mathematics subjects. The method applied by students to tutoring activities is in the form of providing additional mathematics learning hours based on snakes and ladders media as a new form of innovation in learning. The output of this activity is that it is able to increase students' interest in learning mathematics subjects and improve children's mindsets towards mathematics subjects.